Tashmim Barnamaj Android li Ta’ziz Itqan al-Mufradat lada Thullab al-Madrasah al-‘Aliyah: DESAIN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID MENGGUNAKAN APP INVENTOR UNTUK PEMBELAJARAN MUFRADAT DI MADRASAH ALIYAH - Muhammad Jundi (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
The mastery of vocabulary is a crucial aspect in Arabic language learning, as language fluency significantly depends on the command of mufradat. After conducting an in-depth analysis of the problems and needs in the field, several issues were identified, including low proficiency in reading Arabic, inadequate mastery of mufradat, and limitations in the use of learning media by teachers. Therefore, this research aims to design an Android application for vocabulary learning among high school students. This study design is a research and development. The applied model in this research is the Borg and Gall model of research and development, as summarized by Sugiyono. The population of this study is the tenth-grade students at MAN 1 in Gorontalo Regency, and the sample consists of 12 students from class X IPA 2 as the control group and 17 students from class X IPA 3 as the experimental group. The data sources for this study are the students, Arabic language teachers, and experts. The data collection methods used in this study are observation, interviews, questionnaires, and tests. The results of this study are as follows: 1) The researcher designed and developed an interactive Android-based learning application for vocabulary learning. The process of designing and developing multimedia goes through several stages, including problem and need analysis, product design, design validation, design improvement, product testing, improvement, and usage testing. 2) The Android application is effective in vocabulary learning for students. The t-test analysis shows that the t-value of 4.273 is greater than the t-table value of 1.7396, indicating that learning vocabulary using the application is more effective than learning without the application. The use of multimedia learning integrated with students' phones provides better learning outcomes.